Steuerung und Regelung des Lenkradmoments durch Nutzung radselektiver Frontantriebe - Römer, Jürgen (Karlsruher Schriftenreihe Fahrzeugsystemtechnik, 2022)
The use of wheel-individual drives on the steered axle simultaneously enables propulsion and implementation of steering assistance. This work presents a closed-loop and open-loop method for controlling wheel-selective drives with the aim of reducing the steering wheel torque. The proposed optimal linear-quadratic-integral controller achieves a high control quality while ensuring driving safety and reducing energy consumption.